PSYCHOLOGICAL DYNAMICS OF TAROT READINGS DURING THE COVID-19 PANDEMIC - Sukandi, Pipin; Sari, Annur; Amalia, Tesya; Naibaho, Mawar Romian Asi; Shiddiq, Ghifari Fauzul; Nilayamanda, Anak Agung Komang Vijay Manuputra (CENTRAL ASIA AND THE CAUCASUS, 2022)
Psychological dynamics of humans is a unique thing as well as interesting to understand because it is concerned with several aspects that affect. Of course, this has some good and bad sides depending on the condition that occurs, so it causes problems in him if faced with conditions that are not good for the psychological. If this bad condition is not immediately handled properly, it will affect the mindset and attitude so as to make a new habit. The purpose of this study was to look at the psychological dynamics of humans at the beginning until the COVID-19 virus pandemic existed to date using Tarot cards. This research uses quantitative methods with data sources used are data from companies located in the field of Tarot, Journals, Articles and Related Research. The result of this study is, there are psychological changes based on certain factors or conditions at the beginning until now the COVID-19 pandemic exists, which at the beginning of the pandemic people are more likely to economic factors but at this time people are more inclined to romantic relationship factors, this makes a conclusion that economic factors will affect relationship factors in human psychology.